Sekrety panieńskich pokoi. Przedmioty pożądania XIX-wiecznych nastolatek w świetle literatury poradnikowej - Raińska, Kinga (W zwierciadle rzeczy, 2022)
Your own room is a place of rest, relaxation and study. It is a place where no one will disturb us, where you can think about everything in solitude and dream. No wonder that every girl’s dream is to have her own, even the smallest room. It was no different in the 19th century. Every teenager dreamed of independence and a quiet place just for themselves. It was customary in wealthy bourgeois houses to provide a separate room for a young lady who would soon start showing up in company and making contacts. The growing up maiden gave way to the rest of her siblings in the children’s rooms, and she gained a place adapted to her needs. Interestingly, the boys were treated the other way around. They had to share the space with their brothers until they left the family home. To this day, everyone wants to have some privacy, their own little world, where they can „enter” at any time in their life. And no matter what epoch you lived in, most girls dreamt of having a room where they could keep their treasures, souvenirs – things seemingly meaningless to someone, and priceless to themselves.